108 The Impact of Marital Status on Mortality and Length of Stay in Patients Admitted with Myocardial Infarction. (3rd June 2016) - Hayes, Rosie M; Carter, Paul R; Gollop, Nicholas D; Reynolds, Jennifer; Uppal, Hardeep; Sarma, Jaydeep; Chandran, Suresh; Potluri, Rahul
Abstract : Introduction: Ischaemic heart disease is the leading cause of mortality worldwide. The development of surgical and percutaneous interventions has improved survival rates, but the influence of sociodemographic factors on outcomes following MI and their potential use as predictors of such outcomes, are increasingly recognised. Conclusive studies show associations between marriage and lower incidences of IHD in addition to better survival prospects for married individuals suffering MI. There is however, a conflicting evidence base and a lack of literature considering the influence of marital status on LOS, which has been observed to be highly variable in MI patients. Objectives: From a large patient database, we aimed to investigate the impact of marital status on the prevalence, LOS and crude mortality of MI patients admitted in Northern England, UK. Methods: We compared marital status variations and associated LOS and mortality data by one way anova and cox regression respectively, using anonymous information on MI patients obtained from hospitals in North England between 1 st January 2000 and 31 st March 2013. This data was analysed according to the ACALM (Algorithm for Comorbidities, Associations, Length of stay and Mortality) study protocol, which uses ICD-10 and OPCS-4 codes to trace patients and demographics. P values <0.05 were taken as statistically significant. Results: Amongst 929552 patient admissions recorded during the study period there were 25287 cases involving a new diagnosis of MI. Mean age of MI patients was 66.6 years, 64.2% of the cohort were male and 80.3% were Caucasian. 38.2% of MI patients died and mean LOS was 7.0 days. Crude mortality was highest among widowed patients (62.9%). Logistic regression accounting for age, sex and gender showed that married (OR 0.863), widowed (OR 0.959) and unmarried patients (OR 0.973) had statistically lower mortality rates when compared to single people. LOS was statistically shorter for married patients (2.12 days shorter), and unmarried patients (2.66 days shorter) compared to a mean LOS of 8.2days recorded amongst single patients. Conversely, mean LOS was 1.82 days longer for widowed patients. Conclusion: Marital status has a clinically important impact on LOS and mortality of MI patients. In particular, single patients show higher mortality rates and longer LOS compared to married patients. It is reasonable to suggest that these results may be due to reduced social support at home and this should be taken into account when considering the holistic care of patients with MI.